Diversity of bivalves in Tanjung Balai Asahan Waters, North Sumatra, Indonesia - IPANNA ENGGAR SUSETYA; DESRITA DESRITA; ERYANA DHALIA DRAJAD GINTING; MASRIAN FAUZAN; ERI YUSNI; SITI AISYAH SARIDU (Biodiversitas Journal of Biological Diversity, 2018)
Susetya IE, Desrita, Ginting EDD, Fauzan M, Yusni E, Saridu SA. 2018. Diversity of bivalves in Tanjung Balai Asahan Waters, North Sumatra, Indonesia. Biodiversitas 19: 1147-1153. Local and regional market demands for bivalves increase outside Tanjung Balai City and Asahan District Waters, North Sumatra, Indonesia. As a result, high exploitation of bivalves occurred. In the other hand, there were less comprehensive information and studies on the diversity of bivalves in this area. This study aimed to determine the diversity of bivalves and water quality of Tanjung Balai Asahan Waters; was conducted between July 2016 and November 2017. Sampling of bivalves was conducted monthly. Several physical and chemical parameters were quantified. Data analysis included community structure analysis and Principal Component Analysis (PCA). The result showed that there were 16 species of bivalves from 7 families in Tanjung Balai Asahan Waters. Station 2 had the highest composition of bivalves, while the lowest was noted at Station 1. The mean abundance of bivalves at stations 1, 2 and 3 were 352±22 ind/m2, 222±14 ind/m2 and 388±30,2 ind/m2, respectively. In general, the index of diversity was categorized as low to moderate. The evenness index was categorized as low to high, while the dominance index indicated the absence of dominant species at almost all stations except station 1. Water quality of the waters was still in capacity to support the life of bivalves. Based on PCA analysis, it was obtained that the abundance of bivalves was positively correlated with nitrite, nitrate, phosphate, salinity, and pH.